Influence of Green Loans, Corporate Social Responsibility, and Non-Performing Loans on Bank Profitability in Indonesia - Aqib Burhannudin Rizqullah; Wisnu Wibowo (Yayasan Riset dan Pengembangan Intelektual, 2024)
Increasing environmental degradation and climate change caused by inefficient economic activities pose a significant risk to global conditions. This phenomenon has led various countries towards sustainable economies focusing on financial benefits and environmental, social, and governance (ESG). This study analyzes the influence of green loans, corporate social responsibility, and non-performing loans on bank profitability in Indonesia (a case study of first movers in sustainable banking). The study uses panel data from 6 banks in Indonesia covering the period 2017-2022 and estimates using the First Difference Generalized Method of Moments (FDGMM). The results show that green loans positively and significantly impact bank profitability in Indonesia. Corporate Social Responsibility shows no significant impact on bank profitability in Indonesia. Non-performing loans have a negative and significant impact on bank profitability in Indonesia.